PENGARUH FUNDAMENTAL SAHAM & HARGA EMAS DUNIA TERHADAP HARGA SAHAM PERUSAHAAN - Adinda Asma'Syta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Changes in profit can be affected by increased income, one way to increase revenue in mining companies is the price of products sold in the market increases and a good stock fundamental performances, this will affect investor interest and increase stock prices. This research is a type of quantitative causality research. Previously PT Aneka Tambang Tbk became a limited liability company on July 5, 1968 following the merger with several single commodity mining companies such as State General Mining Company, Tjikotok State Gold Mining Company, State Bauxite Mining Company, State Precious Metals Company, Diamond Project, PT Nickel Indonesia, and others. Based on the results of data analysis and processing research on the influence of stock fundamentals and the world gold price of PT Aneka Tambang Tbk has different effects on its stock price. The EPS and World Gold Prices variables that have a positive effect on the stock price of PT Aneka Tambang Tbk, shows that the sentiments of these listed investors prefer stock valuation indicator or divident policies and commodity prices for their investment decision analysis. Both of these have a direct impact on the company's revenue and profits.